241 Is There a Role for Empirical Treatment of Orthopaedic Patients with Suspected, but Not Confirmed, VTE in the Post-Operative Period?. (28th February 2022) - Menon, D.; Abcha, O.; Kallel, S.; Pandit, H.
Abstract: Introduction: Major surgery, including major orthopaedic surgery, is a key risk factor for developing venous thromboembolism (VTE). This poses a challenge in the post-operative phase when considering initiation of therapeutic-dose anticoagulation for suspected VTE due to the risk of major bleeding. Method: A search strategy was developed with inclusion criteria involving all studies relating to the treatment of suspected VTE in the post-operative orthopaedic patient. Journal articles predating 3 rd June 2021 were searched for in Medline, Embase and PubMed. Titles and s were reviewed based on clinical relevance. Results: 56 articles were generated using this search strategy. 22 results were excluded as conference papers and/or case reports. Title and review of the remaining 34 studies did not identify any relevant articles reporting outcomes. Conclusions: No evidence is available to guide recommendations for the empirical treatment of suspected VTE in the post-operative orthopaedic patient prior to a confirmed VTE diagnosis. This is therefore a risk-benefit clinical decision to be undertaken based on individual patient factors. Current American College of Chest Physicians guidelines advise initiation of anticoagulation for suspected acute VTE in cases with a high clinical suspicion, or intermediate clinical suspicion with expected delay in diagnostic imaging for at least 4 hours. However, this does not apply to patients following recent surgery who are at increased risk of bleeding post-operatively. Empirical systemic treatment dose anticoagulation for VTE in the post-operative period should therefore only be initiated when timely image-based diagnosis cannot be achieved.